Integrated Approaches to Managing Cystic Fibrosis: From Nutritional Optimization to Therapeutic Advancements - Salehe Akhondian; Saeedeh Talebi (Reviews in Clinical Medicine)
Background: Cystic fibrosis (CF) is associated with numerous nutritional and health challenges that significantly impact the patient's quality of life and clinical outcomes. Nutritional management plays a vital role in addressing issues such as pancreatic insufficiency, fat malabsorption, vitamin and mineral deficiencies, and complications like CF-related diabetes (CFRD) and liver disease (CFLD). This review provides an overview of the essential nutritional assessment, management strategies, and the role of CFTR modulator therapies in improving the nutritional status and health outcomes in CF patients.Methods: A comprehensive review of the current literature regarding the nutritional needs, deficiencies, and therapies in CF patients was conducted, including a focus on pancreatic enzyme replacement therapy (PERT), vitamin and mineral supplementation, and the management of bone disease, CFRD, and CFLD. Additionally, the impact of CFTR modulators on nutritional outcomes and related complications was examined.Results: Nutritional assessment in CF is multifaceted, incorporating clinical, anthropometric, body composition, and biochemical evaluations. Early intervention strategies, including PERT and tailored supplementation, are critical for managing fat-soluble vitamin deficiencies, mineral imbalances, and maintaining adequate body mass. The prevalence of CFRD and CFLD significantly impacts CF management, necessitating regular screening and appropriate treatments. CFTR modulator therapies have led to improvements in lung function and nutritional status, though regular monitoring is essential to prevent complications such as hypervitaminosis, altered lipid metabolism, and insulin sensitivity.Conclusion: A proactive, individualized approach to nutritional management is essential in CF, emphasizing early intervention, regular screening, and personalized therapy to address the diverse challenges faced by these patients.